Effect of different shot peening conditions on the fatigue life of 300 M steel submitted to high stress amplitudes. (January 2020) - Bag, Amrita; Delbergue, Dorian; Ajaja, Jihane; Bocher, Philippe; Lévesque, Martin; Brochu, Myriam
Highlights: High compressive residual stresses- low roughness causes subsurface crack initiation. Low compressive residual stresses-high roughness delays short crack propagation. Stress-intensity factor-based model can predict the fatigue crack initiation site. Knowledge of material cleanliness is essential to determine benefit from peening. Sole use of statistical analysis to choose optimum peening condition can be misleading. Abstract: The axial fatigue life of 300 M steel subjected to a high stress amplitude was investigated for 3 peening conditions. Peening-induced roughness, residual stresses and their relaxation during cyclic loading were quantified. B-basis analysis was employed to compare the peened and unpeened specimens' fatigue lives. It was observed that a competition between the detrimental effect of roughness and the beneficial effect of compressive residual stresses determines the fatigue crack initiation site. A stress-intensity factor-based approach was proposed to predict a lower bound for fatigue lives. These analytical fatigue life predictions agreed with the statistical B-basis values for conditions exhibiting low scatter.